Three dimensional analysis of pounding between adjacent buildings - Rajaram, Chenna; Kumar, Ramancharla Pradeep (Journal of Structural Engineering, 2024)
During past earthquakes many buildings suffered severe structural damage. Besides damage due to inadequate design and execution, buildings and building components suffered damage due to pounding also. Pounding is defined as collision between two buildings or different parts of the same building leading to severe damage or even sometimes complete collapse. In addition to simple lateral collision, buildings may also collide in torsion mode arising due to eccentricity of mass and stiffness, causing severe damage to adjacent building. In this paper two single storey reinforced concrete buildings are considered. To study the torsional effects due to pounding, buildings with different setbacks and unequal storey levels are analyzed using SAP 2000. The effect of collision is more when structures are kept at extreme levels of setback. At different elevation levels, the pounding response changes significantly than the structures at same elevation levels. More collision force is generated at mid height of column level than other height levels because of shear amplification.